The automatic selection of hydraulic spray nozzles based on the psychrometric air conditions in hydropneumatic sprayers - Shigueaki Sasaki, Robson; de Brito, Ana Cláudia; Batista de Alvarenga, Cleyton; Martins Teixeira, Mauri; Alves Rocha, Helton John (Revista Ceres, 2025)
The aim of the current study is to develop an electronic system capable of automatically replacing hydraulic spray nozzles, based on psychrometric air conditions such as temperature and relative air humidity, in order to help improving the efficiency of application technologies. The system comprised one microcontroller, two solenoid valves, one temperature and relative humidity sensor, and a control algorithm. The system was installed in a hydropneumatic sprayer adapted with two semi-arcs. One semi-arc was equipped with JA-2 and other semi-arc with CVIA-015 hydraulic nozzles. After the algorithm interpreted the momentary psychrometric air conditions, it activated the JA-2 (when VPD < 20 hPa) or the CVIA-015 nozzle (when VPD > 20 hPa). The system was evaluated based on technical spraying parameters and on the response time to replace the hydraulic nozzle. Based on the results, the smallest-diameter droplets were the most influenced by psychrometric air conditions. VPD > 20 hPa tended to increase the VMD values and to reduce droplet density, although it did not change the SPAN index. The necessary mean time to switch from the JA-2 to the CVIA-015 nozzle was 0.742 s, whereas the necessary mean time to switch from the CVIA-015 to the JA-2 nozzle was 0.684 s.